PATIENT SATISFACTION ANALYSIS OF HOSPITAL SERVICE QUALITY FUNCTIONAL AND TECHNICAL SERVICE QUALITY IN RSU. ST. ANTONIUS PONTIANAK - Nugroho B31109096, Arief Rino (Jurnal Manajemen Update, 2015)
Hospital St. Anthony is located at Jalan Kh. Wahid Kasyim 249 is a private hospital that offers health care services to the community. The concept of service is one of the goals achieved by the management of the hospital of St. Antonius. The purpose of the service will be achieved if all the components of managers as Director, Nurse, Midwife, Administration and Finance staff can always work together to provide better care to patients and families of patients. Therefore, the hospital is always trying to improve, both in SOP patient care and in terms of improvement of service facilities. The method of writing of this thesis is to conduct a qualitative approach. A qualitative approach was carried out in order to improve the quality of service of functional and technical quality. The study concluded the following: 1) The response to the level of importance of service quality functional and quality of technical services at the hospital. ST. Antonius Pontianak at the high category by obtaining the average value of 4.08 and 4.01. This means that the patient feels is important for functional services and technical services, 2) The response of respondents to rate their perceived performance on service quality functional and quality technical services at the hospital. ST. Antonius Pontianak at the high category by obtaining the average value of 4.00 and 3.86. This means that the patient feels is important for functional services and technical services, 3) It is a priority to be fixed in an effort to improve the functional services and technical services at the hospital. ST. Antonius Pontianak which service attributes that are in quadrant A. Quadrant A shows that the grain dimensions of functional services and technical services located in this quadrant needs to be a priority for repair. Grains in this quadrant penangananya needs to be improved, because generally the quality of service that has been granted RSU. ST. Antonius still low perceived performance by respondents when these attributes are very important:. Grains dimensions of functional services and technical services included in quadrant A is the internal relationship that exists between fellow nurses and ability to provide solutions for the health problems faced by inpatients and 4) There are differences in the level of perceived performance of respondents to the functional service quality and quality of technical services at the Hospital. ST. Antonius Pontianak. this is shown by the data processing using the Wilcoxon test where the Sig by 0.02 less than 0.05 (0.02 <0.05). Â  Keywords: Patient Satisfaction, Quality of Service Functional, Technical Service Quality